2022
DOI: 10.33448/rsd-v11i9.31948
|View full text |Cite
|
Sign up to set email alerts
|

Biomass in an industrial boiler: characterizing and reducing waste from the burning process

Abstract: Ashes constitute a waste produced in the heat generation process from bioenergy. This study aimed to improve the biomass energy efficiency used in an industrial boiler. The physicochemical analysis was used to perform improvement in the quality of the biomass for solid fuel. Four biomass types (eucalyptus bark, wood chips, sawdust, and recycled wood waste) were analyzed. The material (ash) was collected every two months over one year. All samples were characterized regarding proximate analysis, chemical compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Very little was found in the literature on the question of the effect of particle size on pellets' moisture content. Smaller particle diameters might result in a greater rate of mass loss, particularly moisture, thereby reducing the pellets moisture content percentages [5]. In another study by [6], however, it was concluded that particle size distributions generally did not influence the pellet moisture content, moisture absorption during storage, abrasion resistance and thermochemical conversion time.…”
Section: Moisture Content Variation By Particle Sizementioning
confidence: 97%
“…Very little was found in the literature on the question of the effect of particle size on pellets' moisture content. Smaller particle diameters might result in a greater rate of mass loss, particularly moisture, thereby reducing the pellets moisture content percentages [5]. In another study by [6], however, it was concluded that particle size distributions generally did not influence the pellet moisture content, moisture absorption during storage, abrasion resistance and thermochemical conversion time.…”
Section: Moisture Content Variation By Particle Sizementioning
confidence: 97%